Campus partnership in Information Literacy: the case of faculty Liaison Librarian - Abu Bakar, Ahmad Bakeri; Omar, Fazli (IFLA, 2013)
Without information literacy, library users are unable to effectively recognize what information is needed, how to locate and evaluate the proper information and use it effectively. Once information skills are achieved, users are able to search independently, to gather and analyze relevant information from a wide variety of sources. The establishment of Information Service Division in the library was driven by a need to disseminate library services and facilities rendered to faculty. The task has been shouldered by liaison librarian who acts as intermediary between library and faculty members. The division is required to fulfill the quality objective of accomplishing at least 95% of requests for information literacy workshops. The effectiveness of information literacy workshop is measured by achieving at least 90% of customer satisfaction. The greatest challenge in teaching information literacy is motivating students to be receptive to the theory and practice of the syllabus. This issue is not always viable as the students are already overloaded with daily class schedule. Nevertheless, to design the content and deliver quality and effective information literacy workshop is not an easy task as they need to be constantly re-evaluated to meet the demands of the users. The objective of this study is to evaluate the effectiveness of information literacy programme based on the new partnership between the faculty and the library. The survey questionnaire is used to gather feedback from users who attend the information literacy workshop which is distributed right after the session ends. There are 152 sessions of workshop with a total number of 5133 surveys were collected starting from January until December 2012. The final results of 5358 or 95.3% useful questionnaire were analyzed. The findings show that the division is able to fulfill 100% of information literacy request and successfully achieved its quality objective of customer satisfaction by 99.9%.